Burnout Syndrome dan Faktor-Faktor yang Mempengaruhinya - Ahmad Firdaus; Sakinah Sakinah; Anisah Anisah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to examine the burnout syndrome and the factors that influence it, the sample in this study were employees of the marketing and service divisions in the banking sector in the city of Jambi. The data collection method is using a questionnaire and analyzed using verification analysis, the analytical tool in this study is using structural equation modeling. The results of this study will explain whether or not there is an influence of the factors studied on the high or low burnout syndrome experienced by individuals at work.